Ultrasound Assessment of Synovial Thickness of Some of the Metacarpophalangeal Joints of Hand in Rheumatoid Arthritis Patients and the Normal Population - Manik, Z.H.; George, J.; Sockalingam, S. (Hindawi Publishing Corporation, 2016)
Objective. To compare ultrasound synovial thickness of the 2nd, 3rd and 4th metacarpophalangeal joints (MCPJ) in a group of patients with proven rheumatoid arthritis (RA) and a control group of normal individuals. Materials and Methods. This is a cross-sectional study comprising 30 rheumatoid arthritis patients and 30 healthy individuals. Ultrasound scans were performed at the dorsal side of 2nd, 3rd, and 4th MCPJ of both hands in RA patients and the healthy individuals. Synovial thickness was measured according to quantitative method. The synovial thickness of RA patients and healthy individuals was compared and statistical cut-off was identified. Results. Maximum synovial thickness was most often detected at the radial side of the 2nd MCPJ and 3rd MCPJ and ulnar side of the 4th MCPJ of both hands which is significantly higher () in RA patients compared to healthy individuals. With high specificity (96%) and sensitivity (90%) the optimum cut-off value to distinguish RA patients and healthy individuals’ synovial thickness differs for the radial side of the 2nd and 3rd MCPJ and ulnar side of the 4th MCPJ. Conclusion. Patients with early RA appear to exhibit a characteristic pattern of synovitis which shows radial side predominance in the 2nd and 3rd MCPJ and ulnar side in the 4th MCPJ.